2007
DOI: 10.1038/sj.pcan.4500988
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing cryoablation and external beam radiotherapy for T2C-T3B prostate cancer

Abstract: The objective was to evaluate the relative efficacy of cryoablation (CRYO) versus external beam radiation (EBRT) for clinically locally advanced prostate cancer in a randomized clinical trial. Patients with histologically proven, clinically staged as T2C, T3A or T3B disease were randomized with 6 months of perioperative hormone therapy to one of the two procedures. Owing largely to a shift in practice to longer term adjuvant hormonal therapy and higher doses of radiation for T3 disease, only 64 out of the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 17 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…Chin et al 18 reported a lower biochemical disease-free survival rate at 4 years in CRYO-treated patients than in EBRT-treated patients (13% versus 47%). However, their trial was limited to patients with locally advanced disease and, thus, is not comparable to our trial, which explicitly excluded that patient population.…”
Section: Discussionmentioning
confidence: 98%
“…Chin et al 18 reported a lower biochemical disease-free survival rate at 4 years in CRYO-treated patients than in EBRT-treated patients (13% versus 47%). However, their trial was limited to patients with locally advanced disease and, thus, is not comparable to our trial, which explicitly excluded that patient population.…”
Section: Discussionmentioning
confidence: 98%
“…Targeted cryoablation of the prostate (TCAP) has emerged as an accepted therapy for both primary treatment of clinically localized CaP, as well as for salvage therapy following failed definitive therapy, demonstrating survival and cancer-control at least equivocal to external-beam radiotherapy (3)(4)(5)(6)(7). Erectile dysfunction (ED) and voiding dysfunction are common following all potentially curative CaP treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly fewer positive biopsies were documented after cryoablation than after radiation therapy (7.7% vs. 28.9%). For localized and locally advanced disease (T2c-T3b) with a mean follow-up of 37 months, Chin et al [11] compared 33 patients who underwent cryoablation and 31 patients who received radiotherapy. All patients received three months of neoadjuvant and three months of adjuvant ADT using GnRH agonist monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cryosurgical ablation of the prostate with shortterm ADT for 3-6 months had been utilized in several series, mainly for the purpose of comparison with radiotherapy [10][11][12]. However, in terms of ADT in a combination strategy, the method and duration has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%